A Circumscribed Commemoration: Mrs. Rudolph Anderson and the Canadian Arctic Expedition Memorial - Cavell, Janice (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2012)
In 1926 a plaque commemorating the sixteen men who died during the Canadian Arctic Expedition, 1913–1918 (CAE) was unveiled. The expedition was highly controversial because of the deep divide between the leader, Vilhjalmur Stefansson, and the scientists of the expedition, many of whom were civil servants. Despite their official positions, the scientists were under constraints that blocked their efforts to secure public recognition of their dead colleagues’ services to Canada. Belle Allstrand Anderson, the wife of scientist Rudolph Anderson, was theoretically under even more stringent constraints. Yet, using her persona of devoted wife and her connections with the bereaved families — especially the wives and mothers of the dead men — she successfully negotiated the creation of the memorial. The personal and gendered element in its history gives the CAE memorial an unusual position among state-sponsored commemorations. Recent scholarship has placed increasing emphasis on the role played by intimate domestic relations in the history of polar exploration. Drawing on the Andersons’ extensive personal archive, this paper examines the interplay between the domestic and the political in the commemoration of what was perhaps the most significant twentieth-century Canadian venture in the Far North.